A cross-sectional study on satisfaction with teleconsultation in people with diabetes during the COVID-19 pandemic in semi-urban and village parts of Kerala - B., Jayakrishnan (International Journal of Research in Medical Sciences, 2022)
Background: Since the emergence of the pandemic situation, there has been a gradual paradigm shift in the clinical management of diabetes, wherein, the scheduled clinical visits have been converted into teleconsultations. Patient satisfaction is an important parameter which is not well understood. The aim of the study was to assess patient satisfaction with diabetes management through teleconsultation in these populations. Methods: This cross-sectional study was conducted in the Safe Care clinic in Tirur, Kerala from March 2021 to August 2021. This study included 163 T2D patients who availed of teleconsultation. Patient satisfaction was obtained through an online 12-item questionnaire developed by the authors and administered online via a survey tool. Results: In this study, 60% of the patients were male. The majority of the teleconsults occurred in the 41-60 years age group. Of the 163 responses obtained, 145(88.9%) of patients were satisfied with the explanation provided by their physician about their condition, while 148 (90.7%) were satisfied with the duration of the consultation. Further, 158 (96.9%) would be happy to use teleconsultation again, while 155 (95%) would recommend teleconsultation to their friends and family. Around 150 (92%) feel their confidentiality is maintained similar to in-clinic face-to-face consultation and 98 (60%) opined they would continue to use teleconsultations even after face-to-face interactions resume post-pandemic. Conclusions: The patient satisfaction results of the study indicate that telemedicine is there to stay during and beyond the COVID-19 pandemic for the management of diabetes in the sub-urban and village populations in Kerala.